An Overview of Justicia adhatoda: A Medicinal Plant but Native Invader in India - Isha; Pardeep Kumar; Anand Narain Singh (Conservation)
Justicia adhatoda, also known as Adulsa or Vasaka, is a notable member of the family Acanthaceae, with a broad geographic distribution across varied climatic conditions, and is known for its extensive medicinal properties for treating respiratory disorders, tuberculosis, malaria, and dysentery. It possesses several pharmacological activities, including anti-bacterial, anti-fungal, and anti-cancerous ones. In addition to discussing its morphology, phytochemistry, and pharmacological aspects, the present review also focuses on its several unexplored facets, such as pollination mechanism, cytology, molecular and genetic aspects, conservation, and ecological attributes. The literature survey indicates that, despite its medicinal value, J. adhatoda is also a strong invader in various ecosystems, suppressing associated species and cause vegetation homogenization. It also provides several ecosystem services, including soil stabilization, ecological restoration, and phytoremediation by removing contaminants such as chromium and mercury from wastewater. Additionally, its leaves increase the nitrogen content in compost, promote the proliferation of earthworms, and help suppress plant diseases. This highlights its potential for sustainable land management and integrated disease control. The urgency of this research is underscored by the significant gap in the literature regarding the ecological interactions of J. adhatoda, particularly its allelopathic effects on other plant species. The findings underscore the need for sustainable utilization and conservation strategies, emphasizing the dual importance of J. adhatoda as a medicinal resource and an ecological disruptor.